2016
DOI: 10.1016/j.ces.2016.08.028
|View full text |Cite
|
Sign up to set email alerts
|

From single drop coalescence to droplet swarms – Scale-up considering the influence of collision velocity and drop size on coalescence probability

Abstract: Coalescence modelling in liquid/liquid dispersions is a challenging task and field of investigations up to now, which becomes apparent when comparing the various existent models with their different and partly even contradictive implementation of influencing factors. In this work, systematic investigations of single drop coalescence were used to compare and validate different coalescence efficiency models regarding the important influencing parameters relative collision velocity and drop size. The impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
(157 reference statements)
1
25
0
Order By: Relevance
“…A variety of models to describe coalescence have been proposed, for which recent extensive overviews are available , , , . Here, only those aspects relevant for this work are summarized.…”
Section: Different Principal Approaches To Describe Coalescencesupporting
confidence: 59%
See 3 more Smart Citations
“…A variety of models to describe coalescence have been proposed, for which recent extensive overviews are available , , , . Here, only those aspects relevant for this work are summarized.…”
Section: Different Principal Approaches To Describe Coalescencesupporting
confidence: 59%
“…has to be extended for an additional effect observed experimentally. Kamp as well as Lehr and Mewes evaluated the coalescence probability between individual drops and bubbles, respectively. The authors found that for high relative velocity the coalescence probability is close to zero.…”
Section: Coalescence Model Adapted For Technical Equipmentmentioning
confidence: 89%
See 2 more Smart Citations
“…The development of combined CFD/PBE models has provided unprecedented insight into the fundamentals of bubbly flows . Population balance models give a realistic representation of the behavior of the bubbles and phase interfaces, while CFD provides local information regarding flow and liquid phase turbulence . The population balance models do contain a number of correlations based on experimental observations, such as semiempirically derived models for bubble coalescence and break‐up.…”
Section: Introductionmentioning
confidence: 99%